2011
DOI: 10.1002/sia.3863
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology of a Cu substrate flattened by a 2″ photoemission‐assisted ion beam source

Abstract: Photoemission-assisted plasma irradiation of a 2 00 Cu substrate was performed to clarify the effect of ion impingement on the substrate. With the use of a photoemission-assisted plasma apparatus, the photoemission-assisted plasma was evaluated by optical emission spectroscopy and discharge characteristics. The density ratio of Ar ions and atoms increases with increasing the bias voltage of photoemission-assisted plasma. Changes in the surface morphology of the substrate were investigated using atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Photoemission-assisted low-pressure plasma generation was reported in previous studies for synthesizing nanographite and diamonds as well as flattening material surfaces. [20][21][22][23] DC gas discharge was generated using photoelectrons from a substrate irradiated with vacuum UV light (wavelength: 172 nm) from a Xe excimer lamp. The plasma was generated from the photoelectrons in the Townsend discharge mode.…”
mentioning
confidence: 99%
“…Photoemission-assisted low-pressure plasma generation was reported in previous studies for synthesizing nanographite and diamonds as well as flattening material surfaces. [20][21][22][23] DC gas discharge was generated using photoelectrons from a substrate irradiated with vacuum UV light (wavelength: 172 nm) from a Xe excimer lamp. The plasma was generated from the photoelectrons in the Townsend discharge mode.…”
mentioning
confidence: 99%
“…In a previous paper, it was reported that mechanically grinded Cu surfaces were successfully flattened from 189 to 117 nm in arithmetic average roughness, R a . 18) In this letter, we report a comparative study of the morphological changes of a Cu surface with an initial R q of 2-5 nm processed with Ar + and Xe + ions at E ion = ∼26 eV. Irrespective of the small values of Y S , ∼10 −3 atoms/ion, significant changes of R q were observed: severe roughening from 2.27 ± 0.04 to 4.48 ± 2.20 nm for processing with an Ar + ion source, and significant flattening from 2.89 ± 0.07 to 1.37 ± 0.08 for processing with a Xe + ion source.…”
mentioning
confidence: 99%
“…The PAP ion source with a Xe excimer lamp (USHIO, Head-on type UER20H-172A) with hν = 7.2 eV, available for processing 3 inch wafers, was described in detail in Ref. 18. Cu films with a thickness of 500 nm were deposited on the 3 inch Si wafers with a Ti buffer layer with a thickness of 100 nm by RF magnetron sputtering.…”
mentioning
confidence: 99%